Academic freedom and an invitation to promote its advancement. (28th July 2019) - Bartel, Robyn
Abstract: Academic freedom is under threat internationally. Several high profile incidents suggest that academic freedom is a principle neither well understood nor appreciated by key decision makers and stakeholders whom one might expect to champion it, be they in government or within the academy itself. Among those incidents are the arbitrary exercise of ministerial discretion to override the Australian Research Council expert peer review recommendations for allocation of funding, recent attacks on the credibility of academic publishing internationally, and the atrocious treatment of scholars by authoritarian regimes across the globe. In light of such developments, the membership of the Institute of Australian Geographers recently adopted a resolution that, inter alia, called on the Council of the Institute of Australian Geographers 'not to be silent on the issue of attacks on critical scholarship, academic freedom and the integrity of academic procedures in higher education, research and publishing'. Given the complexity of the issues, this paper invites further discussion and debate on how Australian geography and geographers might better appreciate and advance academic freedom including via the promotion of scholarship that gives full effect to the principle.